Peningkatan Hasil Belajar Sub Tema Indahnya Persatuan dan Kesatuan Negeriku melalui Strategi Giving Question And Getting Answer Dikombinasikan Dengan Media Puzzle - Pujianto, Pujianto (Jurnal Inovasi Pembelajaran di Sekolah, 2022)
The value of learning outcomes in thematic learning in class IV of SD Negeri Bandarharjo 01 Semarang City based on the results of several student daily tests is still lacking. The results of this study can be seen from the results of the average score of each student on four daily tests, namely 59.8, where the average student lacks the sub-theme of the beauty of the unity and integrity of my country, the method used in the learning material is not appropriate for the use of inappropriate media or even not using the media at all, teacher motivation towards student learning is still lacking, and traditional learning also makes the value of learning completeness so far still far from ideal. Learning media with puzzle media carried out in thematic learning sub-theme of the beauty of the unity and integrity of my country in class IV SD Negeri Bandarharjo 01 Semarang City is very helpful in increasing understanding, presenting data in an interesting and reliable manner, making it easier to interpret data and obtain the necessary information. This study is intended to answer the problem, namely whether the strategy of giving questions and getting answers combined with puzzle media can improve learning outcomes for the sub-theme "The Beauty of Unity and Unity of My Country" in class IV SDN Bandarharjo 01 Semarang City in the 2021/2022 Academic Year? These problems are discussed through classroom action research which is carried out through 2 cycles with each cycle the stages are planning, action, observation and reflection. The results showed that the application of the strategy of giving questions and getting answers combined with puzzle media could improve learning outcomes in the sub-theme of the beauty of unity and unity of my country in class IV SD Negeri Bandarharjo 01 Semarang City, Academic Year 2021/2022 This year can be seen from the increase in learning outcomes per cycle, in the pre-cycle 15 students or 54% experienced an increase in cycle I, namely 21 students or 75% and in cycle II there were 25 students or 89%, this shows that the learning carried out was successful and in accordance with the indicators that have been 85% has been met. The increase also occurred in the active learning of students in cycle I, there were 21 students or 75%, there was an increase in cycle II, namely there were 26 students or 93%. 85%.